2017
DOI: 10.1140/epjc/s10052-017-4637-8
|View full text |Cite
|
Sign up to set email alerts
|

Quark stars in $$f(T, \mathcal {T})$$ f ( T , T ) -gravity

Abstract: We derive a working model for the TolmanOppenheimer-Volkoff equation for quark star systems within the modified f (T, T )-gravity class of models. We consider f (T, T )-gravity for a static spherically symmetric spacetime. In this instance the metric is built from a more fundamental tetrad vierbein from which the metric tensor can be derived. We impose a linear f (T ) parameter, namely taking f = αT (r ) + βT (r ) + ϕ and investigate the behaviour of a linear energy-momentum tensor trace, T . We also outline t… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
36
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 62 publications
(38 citation statements)
references
References 34 publications
(56 reference statements)
0
36
0
Order By: Relevance
“…Also, in a further work, the analysis presented here can be performed in models of nonminimal torsion-matter coupling, like those in References [65,66]. While the hydrostatic equilibrium of quark stars has already been performed in such models [67], the application for neutron stars and WDs still lacks.…”
Section: Discussionmentioning
confidence: 99%
“…Also, in a further work, the analysis presented here can be performed in models of nonminimal torsion-matter coupling, like those in References [65,66]. While the hydrostatic equilibrium of quark stars has already been performed in such models [67], the application for neutron stars and WDs still lacks.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, some regular black hole solutions (perturbatively and exact) have been found correctly in [14,15]. When one considers matter, there are some works which have studied the possibility of constructing stars or wormhole solutions in different teleparallel theories of gravity [16][17][18][19][20][21][22][23][24]. Overall the issue of finding exact spherically symmetric solutions in f (T )-gravity is still an open problem.…”
Section: Introductionmentioning
confidence: 99%
“…Still, there are few exact spherically symmetric solutions in modified Teleparallel gravity. Different authors have studied stars and wormholes in different Teleparallel theories [27,[31][32][33][34]. In [20,35], the authors found some vacuum exact solutions in f (T ) gravity, however, they imposed T = constant, which is nothing but consider GR plus a cosmological constant.…”
Section: Introductionmentioning
confidence: 99%